Brain Atrophy in Relapsing Optic Neuritis Is Associated With Crion Phenotype - Cantó, Laura Navarro; Boscá, Sara Carratalá; Vicente, Carmen Alcalá; Gil-Perontín, Sara; Pérez-Miralles, Francisco; Villalba, Jessica Castillo; Nuñez, Laura Cubas; Casanova Estruch, Bonaventura (Frontiers in Neurology, 2019)
Background and objective: Chronic relapsing inflammatory optic neuritis (CRION) is one of the more common phenotypes related to myelin oligodendrocyte glycoprotein antibodies (MOG-Abs). The absence of specific biomarkers makes distinguishing between CRION and relapsing inflammatory ON (RION) difficult. A recent work has suggested a widespread affectation of central nervous system in CRION patients. In order to search for a potential CRION marker we have measured brain atrophy in a cohort of patients, stratified by phenotypes: CRION, RION, and multiple sclerosis with a history of optic neuritis (MS-ON); and MOG-Abs status. Methods: A cross-sectional study was conducted in 31 patients (7 CRION, 11 RION and 13 MS-ON). All patients were tested for MOG and aquaporin-4 antibodies (AQ4-Abs). Clinical data were collected. Brain atrophy was calculated by measuring the brain parenchyma fraction (BPF) with Neuroquant® software. Results: Four of 7 CRION patients, and 1 out 11 RION patients were positive for MOG-Abs (p=0.046) and none MS-ON patients tested positive to MOG-Abs, all patients were negative to AQ4-Abs. The BPF was lower in patients with CRION than patients with RION (70.6 % vs 75.3%, p=0,019) and similar to that in MS-ON patients. Conclusions: Brain atrophy in idiopathic inflammatory relapsing ON is present in patients with CRION phenotype. Data from this study reflect that the optic nerve is a main target involved in these patients but not the only. Our results should be further investigated in larger and prospective studies.